An efficient method for the preparation of N-formyl-imide via amidine using propylphosphonic anhydride (T3P®). Issue 3 (20th January 2016) - Sambaiah, M.; Gudipati, Ramakrishna; Shiva Kumar, K.; Yennam, Satyanarayana; Behera, Manoranjan
Graphical abstract: Abstract: An efficient method for the preparation of N -formyl imide via amidine using propylphosphonic anhydride (T3P®) has been described. Using this method many aryl, hetero aryl, alkyl as well as amino acid imides were synthesized in high yields.